A Study of the Number of Wavelengths Impact in the Optical Burst Switching Core Node - Hani A. M. Harb; Waleed M. Gaballah; Ahmed S. Samra; Ahmed Abo-Taleb; Arief Marwanto (IAES Indonesia Section, 2017)
In Wavelength Division Multiplexing (WDM), several wavelengths run on an optical fiber link that connects two optical switches. The multiple wavelengths are exploited that minimized the contention problem in the Optical Burst Switching (OBS) core node. Mathematical model is used in order to investigate the impact of the wavelengths numbers OBS core node. Two performance metrics are proposed such as the steady-state throughput and the probability of burst loss using steady- state occupancy probabilities and Poisson traffic model arrivals. Numerical results show that at different values of network traffic and some design parameters such as wavelength conversion capability and the mean arrival rate could reveal the OBS performance.